O processo de institucionalização das práticas de responsabilidade social: um estudo de caso na Empresa Viação Urbana Ltda - Sousa, Maílton Galdino de (2006)
The competitive increase and the pressure exerted by the multiple stakeholders of an organization have become growing the accounts rendered of the companies, concerning their social role into the environment they are inserted in. In order to give response to these pressures, many companies have developed strategies and practices of Business Social Responsibility (BSR). The present study aims at understanding the dynamics of the institutionalization of Business Social Responsibility, according to the view of both collaborators and administrators directly involved in the process. In order to do so, it was applied a case study at Viação Urbana Ltda. Company, with data collected of three administrators, by means of semi-structured interviews, and eight collaborators, by means of a questionnaire, chosen due to their strategic role in dealing with the actions of BSR. In addition, by means of a research in the internet, it was used the official site of the company as a source of data. It was noticed that, in the administrators’ view, the practices of the Business Social Responsibility –BSR had already been developed by the company by means of isomorphic processes. But, it was verified that the institutionalization process of these practices is still incipient, although it has already some efforts to the formalization, systematization and measurement, as shown by the policies that the company has developed in this area. However, in the collaborators’ view, in some aspects, there are disagreements with the discourse presented by the administrators, what does not invalidate the actions developed by them, in relation to the introduction and the development of the practices of BSR.